15, 16-Dihydrotanshinone I suppresses IgE-Ag stimulated mouse bone marrow-derived mast cell activation by inhibiting Syk kinase. (1st July 2015) - Li, Xian; Yang, Ju Hye; Jin, Ye; Jin, Fansi; Kim, Dong-Young; Chang, Jae-Hoon; Kim, Jung-Ae; Son, Jong-Keun; Moon, Tae Chul; Son, Kun Ho; Chang, Hyeun Wook
Abstract: Ethnopharmacological relevance: 15, 16-Dihydrotanshinone I (DHT-I), isolated from the dried root of Salvia miltiorrhiza Bung, which is traditionally used to treat cardiovascular and inflammatory diseases agent in Chinese medicine. DHT-I has been reported to have a broad range of biological activities, including antibacterial activity, and has been used to treat circulatory disorders, hepatitis, inflammation, cancer, and neurodegenerative diseases. Aim of the study: The aim of this study was to evaluate the anti-allergic inflammatory effects of DHT-I on degranulation and on the generation of eicosanoids, such as, prostaglandin D2 (PGD2 ) and leukotriene C4 (LTC4 ), in IgE/Ag-stimulated bone marrow-derived mast cells (BMMCs). Materials and methods: The anti-allergic inflammatory activity of DHT-I was evaluated using BMMCs. The effects of DHT-I on mast cell activation were investigated by following degranulation and eicosanoid generation using ELISA and immunoblotting and immunoprecipitation techniques. Results: DHT-I at a concentration of 20 μM markedly inhibited degranulation and the generation of PGD2 and LTC4 in IgE/Ag-stimulated BMMCs (about 90% inhibitions, respectively). Analyses of FcεRI-mediated signaling pathways demonstrated that DHT-I inhibited the phosphorylations of spleen tyrosine kinase (Syk) and linker for activation of T cells (LAT), and inhibited downstream signaling process, including [Ca 2+ ]i mobilization induced by the phosphorylation of phospholipase Cγ1 (PLCγ1), and the activations of mitogen-activated protein kinases (MAPKs) and the Akt-nuclear factor-κB (NF-κB) pathway. Conclusions: DHT-1 inhibits the release of allergic inflammatory mediators from IgE/Ag-stimulated mast cells by suppressing a FcεRI-mediated Syk-dependent signal pathway. This result suggests DHT-I offers a novel developmental basis for drugs targeting allergic inflammatory diseases. Graphical abstract: